INFLUENCE COMPENSATION, MOTIVATION AND COOPERATION TEAM ON EMPLOYEE PERFORMANCE AT THE MEDAN SELAYANG DISTRICT OFFICE - Sihombing, Martha Zepania; Manalu , Tesalonika Agastha; Br Ginting, Dwi Grace Lorencya; Agnadira , Anasya; Simanjorang , Jurisman; Sitorus , Sunday Ade (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The phenomenon of employee performance decline caused by compensation, motivation, and teamwork. The purpose to investigate and evaluate how teamwork, motivation, and pay affect employee performance at the Medan Selayang Sub-District Office. Quantitative research methodology is used. 76 permanent staff members of the Medan Selayang Sub-District Office made up the study's population and sample. Data was gathered using questionnaires and paperwork. The study concludes that, both together and separately, pay, motivation, and teamwork have a significant impact on employee performance at the Medan Selayang Sub-District Office.